Docetaxel in the treatment of metastatic breast cancer: own experience and review of the literature - Karczmarek-Borowska, Bożenna; Paprota, Krzysztof; Dudek, Maria (Contemporary Oncology/Współczesna Onkologia, 2004)
Multiagent chemotherapy with docetaxel is very effective in the therapy of first or second relapse of breast cancer after radical treatment. This study was aimed at assessing the efficacy of treatment in patients with metastatic breast cancer. From June 1999 to August 2001, 39 patients were treated with 3 regimens: 1) Docetaxel (T) 60 mg/m 2 + Doxorubicin (A) 50 mg/m 2 every 21 days – 27 patients; 2) T 60 mg/m 2 + Cisplatin (D) 50 mg/m 2 every 21 days – 9 patients and 3) T 75 mg/m 2 + Navelbine (N) 25 mg/m 2 on the first and fifth day every 21 days. 217 cycles (2 to 8) were administered. Median age of patients was 46 years (29-62). 28 patients (71.8%) with the first relapse and 11 patients (28.2%) with the second relapse were treated. Multiple metastases and single metastases were found in 69.3% and 30.7% of patients, respectively. The toxicity was acceptable. Two patients (5.1%) had neutropenic fever. There were 23% complete response (CR), 36% partial response (PR) and 23% no change (NC). Eighteen percent had progression. Median response time was 9.3 months, median time to progression was 8 months. Median survival time was 19.9 months. Survival was significantly longer for the first than for the second relapse. The patients with multiple and single metastases had median survival time of 15.1 and 29.8 months, respectively. The response rate was 59%. The regimens used were effective and well tolerated.